Nilai Perusahaan Berdasarkan Kinerja Keuangan, Dividen, dan Pengungkapan Corporate Social Responsibility - Devi Dewayanti; Endang Dwi Retnani (Akuntansi & Ekonomika, 2022)
This research aimed to examine the effect of dividend policy, financial performance, and disclosure of CSR on firm value. The purposive sampling was done to get 11 samples of Property and Real Estate companies with 44 observations. The research result concluded that dividend policy did not affect firm value. It showed how higher the shared dividend won’t affect firm value. In contrast, the financial performance had a positive and significant effect on firm value. This showed that the higher the ROE was, the higher the firm value would be. Additionally, it gave a positive signal for investors to have investment. On the other hand, the disclosure of CSR did not affect firm value. It described how higher the disclosure of CSR won’t affect firm value. In other words, the firm value could be influenced by other factors outside the two variables.